"THE RELATIONSHIP OF MUSIC THERAPY WITH FAMILY PSYCHOLOGY IN REDUCING ANXIETY IN PRESCHOOL CHILDREN IN THE CONDITIONS OF GLOBALIZATION AND INNOVATIVE APPROACHES TO PROVIDE MENTAL HEALTH." (Universal International Scientific Journal, 2026)
This thesis analyzes the scientific basis of the relationship between music therapy and family psychology in reducing anxiety in preschool children. The study examines the psycho-emotional state of children, the family environment, and music therapy methods, and shows their interaction and effectiveness in reducing anxiety.
Keywords: Preschool age, anxiety, music therapy, family psychology, emotional stability.